Characterising a local energy business sector in the United Kingdom: Participants, revenue sources, and estimates of localism and smartness. (15th May 2021) - Fuentes González, Fabián; Webb, Janette; Sharmina, Maria; Hannon, Matthew; Pappas, Dimitrios; Tingey, Margaret
Abstract: Local and decentralised energy initiatives increasingly contribute to decarbonising energy systems. This trend is facilitated by emergence of new actors, ownership modes, business practices, and value sources in energy markets. However, there is no systematic account of the businesses which comprise this emerging sector in the United Kingdom, and there are no standardised criteria for what may constitute a "local", potentially "smart", sector. Through development, and descriptive statistical analysis, of a database of legally-constituted energy businesses, we therefore provide a first characterisation of the local energy business sector in the United Kingdom. We develop qualitative indicators to categorise businesses according to their position in a matrix showing degrees of "localism" and "smartness". Our findings reveal an emergent sector comprising diverse organisations, including those with limited energy market experience. Embryonic business innovations are being translated into various revenue sources. However, most businesses have as yet made limited use of digital systems for smart operation; likewise, despite distinctive forms of localism, many aspects remain to be addressed. This finding implies opportunities for this sector to create value through more extensive orientation to localism and smartness. Further research is needed, using more detailed surveys of a representative sample of local energy businesses. Highlights: We provide the first United Kingdom local energy business sector characterisation. We develop a qualitative assessment of degrees of localism and smartness. A local energy business sector is emerging, comprising diverse organisations. Most businesses have as yet made limited use of digital systems for smart operation. Further development of localism and smartness can strengthen value creation.